PERJALANAN HIDUP CARL LINNAEUS SEORANG DOKTER BANGSA SWEDIA YANG MENJADI PAKAR BOTANI DAN ZOOLOGIKALIBER DUNIA - S Somadikarta (BERITA BIOLOGI, 2007)
A baby boy was born in Rashult, Smoland, Sweden, on 23 May 1707, who later became the world famous Swedish botanist and deservedly be called The World's Father of Taxonomy. The baby was baptized as Carl Linnaeus. According to Swedish customs at that time, the baby should had been named Carl Nilsson (Carl, son of Nils), since his father's name was Nils Ingemarsson (Nils,son of Ingemar Bengtson).When Nils Ingemarsson was enrolling the University of Lund, he had - based on the university rules- to have a family name. He choosed Linnaeus as his family name, and since then Nils Ingermarsson was known as Nils Linnaeus.Carl Linnaeus (hereafter Linnaeus) finished his primary school and Gymansium at Vaxyo. After graduation from the Gymnasium,Linnaeus was trained as dress- and shoemaker before pursuing medical studies at the University of Lund in 1727.A year later he moved to the University of Uppsala. Linnaeus got his medical doctorate from the University of Harderwijk (Holland) on 23 June 1735. Before returning to Sweden, Linnaeus was working and visiting several places. He had the opportunity to meet many outstanding botanists during his visits. When he was working (1735-1737) at "Hartekamp", Leiden, and Amsterdam he published many more new findings compared to those other scientists during that time. Linnaeus returned to Sweden and married Sara Lisa Morea on 26 June 1737. They have seven children (two sons and five daughters). Linnaeus was appointed as Professor at the University of Uppsala in 1739 and in 1757 he was ennobled by the King of Sweden. In 1763, Linnaeus' health was declining. In the same year Carl Linnaeus, Jr. became Professor at the University of Uppsala replacing his father. Linnaeus died on 10 January 1778 and five years later, Carl Linnaeus, Jr. died on 1 November 1783. Carl Linnaeus, Jr. was buried in his father's grave in the Katedral of Uppsala. Sara Lisa Morea, Linnaeus' wife, sold the valuable Linnaeus' collection to Sir Edward Smith for 1,000 guinea in 1784. Sir Edward Smith, the First President of The Linnaean Society of London, died on 17 March 1828. There after, The Linnaean Society of London, bought the entire Smith's collection for 3,150. The Linnaeus' collection is now housed safely in Burlington House, Picadilly, London.